C3N4 anchored ZIF 8 composites: photo-regenerable, high capacity sorbents as adsorptive photocatalysts for the effective removal of tetracycline from water. Issue 10 (28th April 2017) - Panneri, Suyana; Thomas, Minju; Ganguly, Priyanka; Nair, Balagopal N.; Mohamed, A. Peer; Warrier, K. G. K.; Hareesh, U. S.
Abstract : C3 N4 –ZIF-8 porous architectures are developed for the efficient adsorption and sunlight induced photocatalytic degradation of tetracycline. Abstract : Materials combining the abilities of adsorption and photocatalysis provide a facile solution for pollutant disposal as secondary remediation processes are avoided. Herein, we report a simple strategy for the development of C3 N4 anchored ZIF-8 microcrystals as sheathed architectures for the highly efficient adsorption and sunlight induced photocatalytic degradation of tetracycline from solution. An adsorption capacity as high as 420 mg g −1 of adsorbent was realized for a composition containing 60 : 40 wt% of C3 N4 and ZIF. Subsequently, the adsorbed tetracycline was degraded to over 96% in 1 h of sunlight exposure. The effects of pH and adsorbate concentration are studied and valid adsorption and degradation kinetic models are arrived at. The bifunctional composite thus developed offers a photo-regenerable adsorbent for the effective removal of an emerging hazardous contaminant.